The Paradox Of Authentic Relationships in Service-Learning Involving Prospective Teachers - Mark D. McCarthy (The University of Alabama, 2022)
Developing authentic relationships as a part of service-learning projects is often considered one of the most meaningful outcomes for both student and community participants. In this project, students met with community members who were not native English speakers. The goal was for students to gain experience with linguistic diversity as they trained to become teachers, while also providing a program for community partners to practice English. I found that the competing goals of the program and its single semester timeframe limited the ability for students to invest in developing authentic relationships, despite any guidance I may have offered. Drawing from my critical examination of student reflective writing, I argue that teacher guidance and modeling do not necessarily lead to the successful development of authentic relationships. I conclude with thoughts on collaboration and suggest that students should have a choice about their participation.